Pengaruh Pendidikan Kesehatan dengan Metode Demonstrasi terhadap Peningkatan Pengetahuan Remaja Putri tentang SADARI - Rahma Novianti; Rosi Kurnia Sugiharti; Musmundiroh Musmundiroh; Triseu Setianingsih (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Breast cancer is recognized as a major global health challenge with 2.3 million cases recorded in 2020 and projections indicating a continuous increase until 2040 (WHO), where early detection becomes a crucial preventive measure that can be introduced through breast self-examination (BSE) education, yet the knowledge of adolescent girls regarding BSE remains low, requiring effective health education strategies; this study therefore aimed to assess the impact of health education using demonstration methods on improving BSE knowledge among adolescent girls at SMK Jayabeka 01 Karawang in 2025 by employing a quantitative approach with a pre-experimental one-group pretest–posttest design involving 103 respondents selected through total sampling, utilizing pretest and posttest questionnaires consisting of 20 items, and analyzing the data with the Wilcoxon Signed Rank Test due to non-normal distribution, with the results showing a significant improvement in knowledge after the intervention (p-value = 0.000, p < 0.05) where 85 respondents experienced an increase, 18 showed no change, and none experienced a decrease, while before the intervention most were in the “moderate” category (67%) and afterward the majority (82.5%) moved into the “good” category, thus confirming that health education delivered through demonstration methods is effective in enhancing adolescent girls’ knowledge of BSE and can be recommended as a suitable and sustainable strategy in school-based programs for early detection of breast cancer.